Expressive Speech Acts in Selected English Songs - Abdulkadhim, Yosra Sabah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Language with its various forms and styles is the main tool for communication and continuation, music is a powerful style of the linguistic variety of forms, it acts as a universal tool for conveying emotions, dreams, memories and personal stories or untold tales. It is an engaging device that allow individuals to express their feelings or to articulate their inner thoughts and what might be difficult to say directly or openly, providing a space for unfiltered thoughts and desires. This research explores the ways that artists opt for selecting utterances that carrying illustrations of expressive language in English songs across various styles like pop, rap, and rock. The current research attempts to enable readers to understand how these lyrics demonstrating emotions by employing sets of speech acts. Songs have the magical ability to emotionally affect people and reflex their experiences and may be their sufferings and tribulations about some event or people inspired by or love. That special power of the songs makes them ideal and prosperous field for studying expressive speech acts as expressive acts also totally on point to in the way they show individuals’ emotions and their application in diverse situations. Keywords: Emotions, Expressive, Lyrics, Songs, Speech Acts